Determinants of household saving behaviour in Ghana - Anthony Amoah; Carlos Kokuvi Tetteh; Noble Osei-Bonsu; Paragon Pomeyie; Godson Ahiabor; George Hughes; Ignanpin Kwabenabu; Benjamin Otchere-Ankrah (Cogent Economics & Finance, 2024)
Developing countries generally exhibit low 'saving' (flow concept) and 'savings' (stock concept) rates. The factors underlying household positive or negative saving behaviours in developed and developing countries are not new in the macroeconomic literature. Whereas some determinants are theoretically generic, others are country- or community-specific and worth investigating. In this study, the determinants of household saving behaviour are examined. We obtain the results using primary data from a household survey and a logit econometric model with its associated average marginal effects. Our evidence shows that household income, level of education completed, employment status, and households with launching children (or transitioning older adults) are primary drivers of household saving behaviour in Ghana. Further heterogeneous analysis shows that saving behaviour does not statistically differ by gender but by poverty headcount. In line with the findings of this study, relevant policy prescriptions are discussed. This study contributes to the ongoing discourse on household saving behaviour, specifically within the context of developing countries, by providing empirical evidence from Ghana. Utilising primary household survey data, the research identifies key factors such as income, education level, employment status, and household lifecycle stages (e.g., families with launching children or transitioning older adults) as critical determinants of saving behaviour. The findings offer actionable insights for policymakers in developing economies aiming to boost saving rates, reduce poverty, and promote financial stability. By demonstrating that household saving behaviour varies by poverty headcount rather than gender, the study underscores the need for targeted financial inclusion and education policies. The results are particularly relevant for economic development strategies in countries with similar socio-economic structures, offering a foundation for tailored interventions that can foster more resilient household financial practices. This paper's insights can shape future research and policy development aimed at addressing the unique saving dynamics in developing nations, ultimately contributing to improved macroeconomic stability and individual financial security.
Keywords: 330; behaviour; demographic; Finance; household survey; primary data; regression; Saving